THE QUALITY OF MILK PRODUCED IN "FADHILIA VILLAGE" NEAR BAGHDAD IN IRAQ - H. Najin, N.; M. Alazawi , A.; S. Al-Nassir, H. (The Iraqi Journal of Veterinary Medicine, 1988)
A study on the quality of milk produced in "Fadhilia Village" near Baghdad extending over a period of one year, revealed that the total bacterial and coliform counts for milk samples from individual producers were 7.4x105 and 2.5x103 in summer, and 1.8x10 and 5.4x10 in winter respectively. The above counts for bulk milk samples were 3.3x10 and 1.8x101 in sumer and 5.1x10 and 3.3x103 in winter respectively. All over the year the preliminary incubation and psychrotrophic counts for both individual and bulk milk samples were strictly higher than all the proposed standards. There was a significant drop in methylene blue reduction time in summer samples compared to winter samples. A similar drop was noticed in bulk tank samples as compared to individual producer samples. Besides that a significant increase in lactic acid content in Surner samples compared to winter samples.